The Impact of Smoking on Heart Rate and Blood Pressure: A Two-Week Observational Study - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
This study meticulously analyzed the acute and sub-acute effects of a two-week smoking regimen on heart rate and blood pressure. Participants engaged in a controlled smoking phase, consuming 10 cigarettes daily for one week, followed by a subsequent week of complete abstinence from tobacco. Throughout the study, daily heart rate measurements were meticulously recorded, and blood pressure was assessed on the first and last days of both the smoking and cessation periods to document physiological alterations. The primary objective was to elucidate the exercise physiological perspectives concerning cardiovascular health and autonomic nervous system function, particularly in relation to tobacco consumption and subsequent cessation. The findings underscore the detrimental impact of nicotine on cardiovascular parameters and highlight the rapid, beneficial physiological adaptations observed upon smoking cessation, providing compelling evidence for the immediate health advantages of quitting tobacco.